INSTITUTIONALIZATION OF GENDER MAINSTREAMING IN NIGERIA’S TERTIARY - Aina, Olabisi Idowu; Ogunlade, Ibiyinka; Ilesanmi, Oluwatoyin Olatundun; Afolabi, Comfort (European Scientific Journal, ESJ, 2015)
Women have been historically marginalized in all spheres of life including social, economic and political spheres. This anomaly has been recognized globally and it has become accepted that issues of women’s human rights are important for any meaningful development to take place. Apart from social justice, which demands equal opportunity for all citizens, it is smart economics to plan with both halves of one’s population because it benefits society as a whole. In consonance with this global standpoint, and coupled with Civil Society engagements, the Nigerian government has been overt in engaging in gender responsive policies and programmes, including the development of the National Gender Policy in 2006 which puts credence on strengthening institutions and systems for gender mainstreaming and building partnerships with male led institutions to deliver results for girls and women. The policy recognises gender education as a major pillar in the process of achieving gender equality and women empowerment through transformative development process. Although the process has been somewhat slow, the Nigerian tertiary institutions are now becoming responsive to the engendering process that is, ensuring that academic programmes and the learning environment are gender responsive. Although the gender profile in Nigerian tertiary institutions is still abysmally poor, a number of universities are now adopting gender mainstreaming strategies in knowledge production and in practice. Using Ekiti State University as a case study, the paper presents gender mainstreaming strategies and mechanisms adopted in Nigerian tertiary institutions, noting achievements, challenges and prospects. Basic gender profile of the university is presented, while intervention programmes and initiatives at bridging gender gaps and institutionalising gender mainstreaming as an administrative tool are processed and analysed.